Enhancement of antihydrogen formation in antiproton collisions with excited-state positronium - Kadyrov, Alisher; Rawlins, Charlie; Stelbovics, Andris; Bray, Igor; Charlton, M. (2015)
© Published under licence by IOP Publishing Ltd. Antihydrogen formation in positronium scattering on antiprotons is investigated using the two-centre convergent close-coupling method. A several orders of magnitude enhancement in the formation of antihydrogen is found when positronium is in an excited state. The effect is greatest at the lowest energies considered which encompass those achievable in experiment. This suggests a practical approach to creating neutral antimatter for testing its interaction with gravity and for spectroscopic measurements.